Approaches to triangulation of alcohol data in Scotland: Commentary on Rehm et al. (21st September 2020) - Robinson, Mark; Kibuchi, Eliud; Gray, Linsay; McCartney, Gerry
Abstract: Rehm et al . highlight the ongoing difficulties in accurately estimating alcohol consumption using surveys. Population surveys, in particular, suffer from non‐response and sampling bias, which affects their representativeness, but they are one of the few ways of estimating differences in consumption across population subgroups. In this article, we highlight different approaches that have been taken in Scotland to try to overcome these problems, from the pragmatic to the sophisticated.